2009
DOI: 10.1016/j.joca.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Does isolated patellofemoral osteoarthritis matter?

Abstract: Mild isolated PF OA is significantly associated with symptoms of pain, stiffness and functional limitation. Further research on its recognition in clinical practice and the development of targeted treatments to prevent or slow progression are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 18 publications
8
114
0
Order By: Relevance
“…Contrary to common belief, the PF joint may be a more common site of OA (1,2) and source of symptoms (3,4) than the TF joint. PF joint OA also predicts the incidence of TF joint OA (5,6).…”
Section: Introductionmentioning
confidence: 66%
“…Contrary to common belief, the PF joint may be a more common site of OA (1,2) and source of symptoms (3,4) than the TF joint. PF joint OA also predicts the incidence of TF joint OA (5,6).…”
Section: Introductionmentioning
confidence: 66%
“…However, the brace increased kneeling or squatting. It is associated with pain, stiffness and functional limitation 3,5 .…”
Section: Mmentioning
confidence: 99%
“…Cross-sectional community-based research studies suggest that structural changes consistent with OA may be more common in the PFJ than in the tibiofemoral joint (Lanyon et al, 1998;Duncan et al, 2006;Szebenyi et al, 2006), and are likely to be an important source of symptoms in knee OA (Hunter et al, 2003;Englund and Lohmander, 2005;Kornaat et al, 2006;Duncan et al, 2009). Indeed, one of these showed that approximately a quarter of .50-year-olds who had experienced some knee pain in the past year had isolated patellofemoral OA in at least one of their knees (Duncan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%